The effects of core stability training as injury prevention from low back pain among Malaysian elite sailor athletes / Nur Firzanah Azrul Hisham - Azrul Hisham, Nur Firzanah (2021)
The risk of injury at the spine and lower extremity are more prominent in classes that require the sailor to take part in continuous hiking technique due to subsequent high pressure on the lumbar spine and intervebral disc, along these lines conceivably expanding the risk of injury. Core stability training may enhance the prevention from injury of low back pain that including in improvement in sporting performance among elite athlete sailors. However, there is no study on core stability training for sailing athletes that associated with LBP. The purpose of this study was to investigate the effects of six weeks core stability training (CST) intervention undertaken on 2000-m rowing, isometric back leg strength and flexor endurance as injury prevention for low back pain (LBP) among elite sailing athlete. Eight male elite sailing athletes with no musculoskeletal disorder, aged 21 ± 2.14 years old were involved in this study. Participants were separated into two groups: core stability training (CST) and control group (CON). This study using randomized control trial design. Paired t-test was used to compare pre and post of Visual Analogue Scale (VAS), 2000-m rowing performance, isometric back leg strength and flexor endurance. There was a significant effects on core stability training group when compared for pre and post VAS, (p<0.05). However, there was no significant effects on CST and CON group for pre and post of 2000-m rowing, isometric back leg strength and flexor endurance. In conclusion, this study has still not been convincing in finding a relationship between training of the core and enhancements in physical execution, it would seem that the type of core training program used in this study could be constructive by compliant developments in core endurance and may also be prominent in preventing and reducing occurrences of LBP.